Safety and Immunological Evaluation of Interleukin-21 Plus Anti-α4β7 mAb Combination Therapy in Rhesus Macaques - Pino, Maria; Uppada, Srijayaprakash Babu; Pandey, Kabita; King, Colin; Nguyen, Kevin; Shim, Inbo; Rogers, Kenneth; Villinger, Francois; Paiardini, Mirko; Byrareddy, Siddappa N. (Frontiers in Immunology, 2020)
HIV and SIV infections compromise gut immunological barriers, inducing high levels of inflammation and a severe depletion of intestinal CD4+ T cells. Expression of α4β7 integrin promotes homing of activated T cells to intestinal sites where they become preferentially infected; blockade of α4β7 with an anti-α4β7 monoclonal antibody (mAb) prior to infection has been reported to reduce gut SIV viremia in rhesus macaques (RMs). IL-21 administration in ART-treated, SIV-infected RMs reduces gut inflammation and improves gut integrity. We therefore hypothesized that the combination of IL-21 and anti-α4β7 therapies could synergize to reduce inflammation and HIV persistence. We co-administered 2 intravenous doses of rhesus anti-α4β7 mAb (50mg/kg) combined with 7 weekly subcutaneous infusions of IL-21-IgFc (100g/kg) in 4 healthy, SIV-uninfected RMs to evaluate the safety and immunological profiles of this combined intervention in blood and gut. Co-administration of IL-21 and anti-α4β7 mAb showed no toxicity at the given dosages as assessed by multiple hematological and chemical parameters, and did not alter the bioavailability of nor the generation of antibodies against the anti-α4β7 mAb or IL21-IgFc. Upon treatment, the frequency of CD4 memory T cells expressing β7 increased in blood and decreased in gut, consistent with an inhibition of activated CD4 T cell homing to the gut. Furthermore, the frequency of T cells expressing proliferation and immune activation markers decreased in blood and, more profoundly, in gut. The combined IL-21 plus anti-α4β7 mAb therapy is well tolerated in SIV-uninfected RMs and reduces the gut homing of α4β7+ CD4 T cells as well as the levels of gut immune activation.